New calculation method for tube cross-flow heat exchangers - Węglarz Katarzyna (EDP Sciences, 2021)
A new method for thermal calculations of the cross-flow tube heat exchangers was proposed. The temperature of both fluids and the wall temperature are determined. The heat exchanger is divided into control volumes, in which outlet fluid temperatures are calculated by closed analytical formulas. Two examples of the application of the method for the calculation of two-pass cross-co-current and cross-countercurrent superheaters were presented. An exact analytical model was also developed for both superheaters to estimate the accuracy of the proposed method. The results of the superheater calculations using the developed method are in good agreement with the results obtained by the exact analytical models. The proposed method can be used to calculate heat exchangers with a complicated flow system in which the physical properties of fluids are temperature-dependent.